MENINGKATKAN MOTIVASI KERJA DENGAN PENGHARGAAN BERBASIS KINERJA BAGI AKUNTAN PUBLIK - Kristianto, Djoko (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2010)
Abstrack Management human resource is not an new in environment an organization. Effort human being, non a[n static, but continuing to expand and change rhythm with human life dynamics that goes on in togetherness. Efficacy an institution supported by some factor, among others human resource role, public accountant as part of human resource they need in motivation so that/ to be its performance can mount, for the reason institution have to comprehend the human resource behavior. In a condition that way each management element play important role to utilize organization and exploit resource had so that can detain threat and pressure from environment which is each moment change until as low as possible so that earn process launching attainment of is target of an organization. Keywords : Public accountant, motivation, resource, performance.